2017
DOI: 10.1111/nph.14891
|View full text |Cite
|
Sign up to set email alerts
|

MdWRKY9 overexpression confers intensive dwarfing in the M26 rootstock of apple by directly inhibiting brassinosteroid synthetase MdDWF4 expression

Abstract: Dwarfing rootstocks enable high-density planting and are therefore highly desirable in modern apple (Malus domestica) production. M26 is a semi-dwarfing rootstock that is used worldwide, but identifying intensive dwarfing rootstock is a major goal of apple breeding programs. Herein, we show that MdWRKY9 mediates dwarfing by directly inhibiting the transcription of the brassinosteroid (BR) rate-limiting synthetase MdDWF4 and reducing BR production. We found that the transcriptional factor MdWRKY9 is highly expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 66 publications
(87 reference statements)
1
75
0
Order By: Relevance
“…Several studies have confirmed that WRKY transcription factors are involved in hair development (Verweij et al, 2016), seed size (Luo et al, 2005;Gu et al, 2017), pollen development (Lei et al, 2017), growth types , flowering time , fruit ripening (Cheng et al, 2016) and leaf senescence (Ay et al, 2009;Brusslan et al, 2012;. WRKY transcription factors modulates plant hormone signaling pathways (Liu et al, 2017a;Liu et al, 2017b;Jin et al, 2018;Zheng et al, 2018). Despite the important roles in plant growth and development and signal pathways, the most significant function of WRKY proteins studied thoroughly and reported widely is transcription regulation of response to abiotic and biotic stresses.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have confirmed that WRKY transcription factors are involved in hair development (Verweij et al, 2016), seed size (Luo et al, 2005;Gu et al, 2017), pollen development (Lei et al, 2017), growth types , flowering time , fruit ripening (Cheng et al, 2016) and leaf senescence (Ay et al, 2009;Brusslan et al, 2012;. WRKY transcription factors modulates plant hormone signaling pathways (Liu et al, 2017a;Liu et al, 2017b;Jin et al, 2018;Zheng et al, 2018). Despite the important roles in plant growth and development and signal pathways, the most significant function of WRKY proteins studied thoroughly and reported widely is transcription regulation of response to abiotic and biotic stresses.…”
Section: Introductionmentioning
confidence: 94%
“…The primers are shown in Table S1. The EMSA reaction was performed as described by Zheng et al (2018).…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%
“…The yeast AH109 strain was transformed with pBD-PtFLC and pBD-PtHB13 constructs. The yeast transcriptional activity assay was performed as described previously [41]. Each experiment was independently repeated three times in this study.…”
Section: Transcriptional Activity Assaymentioning
confidence: 99%